Water Co-Adsorption in Ultrathin Films of Ionic Liquids on Pt(111) - Talwar, Timo; Steinrück, Hans-Peter; Maier, Florian (ChemistryOpen, 2025)
The influence of pre-adsorbed water (D2O) on the growth, adsorption, orientation, and thermal behavior of two ionic liquids (ILs) on Pt(111) was studied within the SCILL (solid catalyst with ionic liquid layer) concept. Nonfunctionalized [C1C1Im][Tf2N] and nitrile-functionalized [C3CNC1Im][Tf2N] were deposited at ∼100 K onto clean Pt(111) or onto single-layer and multilayer crystalline (CI) or amorphous (ASW) D2O films and analyzed at various temperatures by angle-resolved X-ray photoelectron spectroscopy (ARXPS). On both clean and D2O-covered Pt(111), the ILs initially grow in a 2D layer-by-layer mode, forming a closed wetting layer at ≈ 0.5 ML IL coverage, followed by moderate 3D growth above 0.8–1.0 ML. At 100 K, the ILs partially displace D2O from the Pt surface, yielding co-adsorption structures where IL contacts Pt(111) directly and is also located in a second layer. [Tf2N]− anions adsorb in cis-configuration with oxygen atoms toward the surface, while the cations adopt mixed parallel and tilted orientations. Heating to 130 K induces rearrangement, increasing direct IL–Pt(111) contact by favoring parallel cation alignment. Co-adsorbed D2O remains but desorbs at ≈10 K lower temperature, indicating weaker binding to Pt. The similar interfacial behavior of both ILs shows that the nitrile group does not significantly influence adsorption geometry or thermal stability.
CRIS-Team Scopus Importer:2025-12-05
Keywords: ARXPS (angle resolved X-ray photoelectron spectroscopy); coadsorption; ionic liquids; SCILL (solid catalyst with ionic liquid layer); water